The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/met.1866
|View full text |Cite
|
Sign up to set email alerts
|

A method for predicting short‐time changes in fine particulate matter (PM2.5) mass concentration based on the global navigation satellite system zenith tropospheric delay

Abstract: In this study, a method of haze prediction has been developed based on zenith tropospheric delay (ZTD). The relationship between ZTD and fine particulate matter (PM2.5, the main component of haze) during hazy periods in Beijing from 2015 to 2018 was analysed. The correlation between ZTD and the PM2.5 series was analysed based on data from three hazy periods with relatively stable weather conditions, no heavy rainfall and relatively continuous data, and the correlation coefficient between ZTD and the PM2.5 seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…So for long-term prediction, adding ZWD cannot perform well. From section I, the accuracy of various hourly PM2.5 concentration monitoring and prediction models is basically between 20μg/m 3 -60μg/m 3 , due to the difference between mathematical models and external factors (such as region, season, climate, time period, PM2.5 source, PM2.5 concentration change range) [21]- [26], [31], [32]. And based on SVMR method with metabolic method, using ZWD and meteorological factors to online predict PM2.5 concentration can be substantially better than 60μg/m 3 within 3 hours and better than 80μg/m 3 within 6 hours in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So for long-term prediction, adding ZWD cannot perform well. From section I, the accuracy of various hourly PM2.5 concentration monitoring and prediction models is basically between 20μg/m 3 -60μg/m 3 , due to the difference between mathematical models and external factors (such as region, season, climate, time period, PM2.5 source, PM2.5 concentration change range) [21]- [26], [31], [32]. And based on SVMR method with metabolic method, using ZWD and meteorological factors to online predict PM2.5 concentration can be substantially better than 60μg/m 3 within 3 hours and better than 80μg/m 3 within 6 hours in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, through the method of Daubechies (DB) wavelet decomposition, it can be found that GPS water vapor reconstructed by low frequency coefficient and PM2.5 concentration sequence has a good correlation in the low frequency domain [30]. With GNSS tropospheric zenith total delay (ZTD), relative humidity, average wind speed, NO2 concentration, establishing multiple linear regression model of PM2.5, through the method of DB wavelet decomposition and reconstruction, can get mathematically meaningful results [31]. With ZTD, air quality pollutants (SO2, NO2) and meteorological factors (wind direction, relative humidity, temperature and wind speed) as input factors, and PM2.5 concentration values as the output factor , Zhou et al [32] establish a neural network model to predict hourly PM2.5 concentration in Guilin.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-derived tropospheric data have a strong correlation with PM 2.5 [37]. To explore the variation patterns presented by PM 2.5 with PWV and ZTD at different time scales at each station in the five provinces of south-central China, data corresponding to 340 PM 2.5 ground stations were mapped and analyzed.…”
Section: Analysis Of the Relationships Between The Original-sequence Ztd And Pwv With Pm 25mentioning
confidence: 99%
“…Guo et al [18] conducted a study on forest fires in northern China to assess the impact of changes in PM2.5 on environmental pollution. Guo et al [19] used the global navigation satellite system (GNSS) for short-term prediction of PM2.5, demonstrating the feasibility of monitoring of particulate matter with GNSS technique. Based on the GNSS and meteorological factors, Wen et al [20] verified the relationship between zenith wet delay (ZWD) and PM2.5, and forecast PM10 values in the short term.…”
Section: Introductionmentioning
confidence: 99%